Evolution of capital structure in East Asia: corporate inertia or endeavours? - Nigel Driffield; Sarmistha Pal (Institute for the Study of Labor (IZA), 2008)
The present paper examines the capital structure adjustment dynamics of listed non-financial corporations in seven East Asian countries during 1994-2002. Compared to firms in the least affected countries, average leverages were much higher among firms in the worst affected countries while the average speeds of adjustment were lower. This general ranking is robust to various alternative specifications and sample selections. We argue that this pattern is closely linked to weaknesses in regulatory environment and lack of access to alternative sources of finance in the worst affected countries.
urn:nbn:de:101:1-2008040918
Keywords: G32; 330; Capital structure dynamics; partial adjustment models; firm- and time-varying speed; generalised methods of moments; inertia and endeavours; Kapitalstruktur; Wirtschaftliche Anpassung; Finanzmarktkrise; Industrie; Ostasien